2010
DOI: 10.1097/jsm.0b013e3181e8f8d8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychological Distress and Baseline Sports-Related Concussion Testing

Abstract: Given the possibility of obscured concussion deficits after injury, implications for premature return to play, and the need to target psychological distress outright, these findings heighten the clinical importance of screening for psychological distress during baseline and post-injury concussion evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 34 publications
(29 reference statements)
1
54
1
1
Order By: Relevance
“…Similarly, pre-injury resilience and depression were predictive of 1-month post-injury anxiety and post-concussive symptoms [54]. Along with prolonging recovery from a concussion, psychological distress has been shown to adversely influence performance on computerized neurocognitive tests which are commonly used to establish a pre-season baseline [55], thus further complicating how emotional distress can influence recovery or detection of clinical recovery.…”
Section: Predictors Of Pcsmentioning
confidence: 97%
“…Similarly, pre-injury resilience and depression were predictive of 1-month post-injury anxiety and post-concussive symptoms [54]. Along with prolonging recovery from a concussion, psychological distress has been shown to adversely influence performance on computerized neurocognitive tests which are commonly used to establish a pre-season baseline [55], thus further complicating how emotional distress can influence recovery or detection of clinical recovery.…”
Section: Predictors Of Pcsmentioning
confidence: 97%
“…Multiple situational factors have been shown to influence baseline test performance. 4,[13][14][15][16] However, the role of supervision in the testing environment has not yet been empirically evaluated, as far as we know. Therefore, the goal of our pilot study was to determine if general self-reported supervision, or lack thereof, affected neurocognitive baseline test performance systematically in high school athletes.…”
Section: Discussionmentioning
confidence: 99%
“…However, these factors rarely fluctuate in the short term and are therefore controlled between baseline and postconcussion tests. 12 In contrast, situational factors, such as psychological distress, 13 group (versus individual) test administration, 4 and motivation (including ''sandbagging''), [14][15][16] are more likely to vary between tests because these factors are harder to control. Unfortunately, many of these situational factors influence baseline test performance as well.…”
mentioning
confidence: 99%
“…If repeat testing indicates invalid or sandbagging profiles, careful discussion with the athlete may reveal factors, such as illness, sleeping problems, attention or learning problems, or psychological distress, that may have contributed to his or her performance. 12,27 For example, student-athletes with histories of special education were more likely to be identified as demonstrating suboptimal effort on testing in our study. Therefore, invalid profiles actually may be valid results, which are lower than the norm because of the legitimately weak cognitive skills of the athlete.…”
Section: Discussionmentioning
confidence: 63%